The The Effect of Health Education With Puzzle On Dengue Hemorrhagic Fever's Prevention Behavior of School Aged - Lestari, Ratna; Putri Fadila, Septiana; Yusriana (STIKES Garuda Putih, 2024)
Background: Dengue Hemorrhagic Fever (DHF) is an infectious disease that require treatment to prevent the mortality. School becomes the target of DHF prevention due to potential location of DHF spread and transmission. Pupils spend more time at school and sometimes pay less attention to their cleanliness environment. Health education by using puzzle is one of strategies to prevent DHF. Purpose: This study aims to find the effect of health education using puzzle on the level of knowledge, attitude, and behavior on DHF prevention before and after health for school age grade IV and V at SD N Sewon 1 Bantul. Methods: This study is quantitative research using pre-experiment approach one group Pretest – Post test. The sample was 52 pupils’ grade IV and V without prior history of DHF selected using total sampling technique. The level of knowledge, attitude, and prevention were measured using a questionnaire given before and after health education using puzzle. Result: The result of analysis using McNemar test showed that the p 0.013 (p < 0.05) for knowledge, p 0.000 (p < 0.05) for attitude, and p 0.002 (p<0.05) for behavior. Conclusion: These means that there is an effect of health education using puzzle on the level of knowledge, attitude, and behavior on DHF prevention. School is expected to give health education on other interested media for any health topic. Keywords : Dengue fever prevention, health education, puzzle